NLRP3 gain-of-function in CD4+ T lymphocytes ameliorates experimental autoimmune encephalomyelitis. (13th September 2019) - Braga, Tárcio Teodoro; Brandao, Wesley Nogueira; Azevedo, Hatylas; Terra, Fernanda Fernandes; Melo, Amanda Campelo L.; Pereira, Felipe Valença; Andrade-Oliveira, Vinicius; Hiyane, Meire Ioshie; Peron, Jean Pierre S.; Camara, Niels Olsen Saraiva
Abstract : NLRP3 inflammasome [NLR (nucleotide-binding domain, leucine-rich repeat containing protein) Pyrin-domain-containing 3 ] functions as an innate sensor of several PAMPs and DAMPs (pathogen- and damage-associated molecular patterns). It has been also reported as a transcription factor related to Th2 pattern, although its role in the adaptive immunity has been controversial, mainly because the studies were performed using gene deletion approaches. In the present study, we have investigated the NLRP3 gain-of-function in the context of encephalomyelitis autoimmune disease (EAE), considered to be a Th1- and Th17-mediated disease. We took advantage of an animal model with NLRP3 gain-of-function exclusively to T CD4 + lymphocytes (CD4CreNLRP3fl/fl). These mice presented reduced clinical score, accompanied by less infiltrating T CD4 + cells expressing both IFN-γ and IL-17 at the central nervous system (CNS) during the peak of the disease. However, besides NLRP3 gain-of-function in lymphocytes, these mice lack NLRP3 expression in non-T CD4 + cells. Therefore, in order to circumvent this deficiency, we transferred naive CD4 + T cells from WT, NLRP3−/− or CD4CreNLRP3fl/fl into Rag-1−/− mice and immunized them with MOG35–55 . Likewise, the animals repopulated with CD4CreNLRP3fl/fl T CD4 + cells presented reduced clinical score and decreased IFN-γ production at the peak of the disease. Additionally, primary effector CD4 + T cells derived from these mice presented reduced glycolytic profile, a metabolic profile compatible with Th2 cells. Finally, naive CD4 + T cells from CD4CreNLRP3fl/fl mice under a Th2-related cytokine milieu cocktail exhibited in vitro an increased IL-4 and IL-13 production. Conversely, naive CD4 + T cells from CD4CreNLRP3fl/fl mice under Th1 differentiation produced less IFN-γ and T-bet. Altogether, our data evidence that the NLRP3 gain-of-function promotes a Th2-related response, a pathway that could be better explored in the treatment of multiple sclerosis.